2013
DOI: 10.5665/sleep.3032
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep and Breast Cancer Incidence among Postmenopausal Women in the Women's Health Initiative

Abstract: This study does not provide strong support for an association between self-reported sleep duration, sleep quality, insomnia, or sleep disturbance with the risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 29 publications
6
75
4
1
Order By: Relevance
“…These findings are supported in numerous population-based studies that have demonstrated robust associations between sleep disturbances and impaired emotional and physical status [2,20,22,[24][25][26][27][28][29][30][31][32][33]. In a cross-sectional study, Grandner et al (2012 [2]) reported that poor general health incurred a fivefold increase in risk for sleep disturbance, whereas moderate to severe depressed mood was associated with ORs of 13.0 and 16.0 in risk for sleep disturbance in women and men, respectively, in adjusted models.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These findings are supported in numerous population-based studies that have demonstrated robust associations between sleep disturbances and impaired emotional and physical status [2,20,22,[24][25][26][27][28][29][30][31][32][33]. In a cross-sectional study, Grandner et al (2012 [2]) reported that poor general health incurred a fivefold increase in risk for sleep disturbance, whereas moderate to severe depressed mood was associated with ORs of 13.0 and 16.0 in risk for sleep disturbance in women and men, respectively, in adjusted models.…”
Section: Discussionsupporting
confidence: 62%
“…Insomnia was defined using the IRS cut point of 9 [22]. This threshold has been widely used in previous studies investigating insomnia and health-related outcomes among WHI cohorts [27][28][29]. Categories of change were constructed based on insomnia statuses at baseline and follow-up (ie, year 1 for the CT, and year 3 for the OS cohorts, respectively).…”
Section: Insomnia Rating Scalementioning
confidence: 99%
“…Interestingly, Qian et al found reduced sleep duration (<6 hours versus 8-≤9 hours per weekday) increased the relative risk (RR) of ER-breast cancers (RR 2.12, 95% CI 1.18-3.82) and reduced the risk of ER+ cancers (RR 0.53, 95% CI 0.33-0.86). However, other epidemiological studies found no clear association between sleep duration and ER status (18,20).…”
Section: Possible Biological Mechanismsmentioning
confidence: 87%
“…Some studies report increased risks for fewer average hours of sleep (15,16), and others find no association or risks increasing with sleep duration (17)(18)(19)(20). While poor sleep may also be associated with lowered melatonin levels, diurnal sleep itself promotes immunological processes through the production of cytokines during sleep and increased levels of white blood cells following sleep (21).…”
mentioning
confidence: 99%
“…Although some studies have found that short sleep duration is related to an increased risk of some types of cancer, particularly breast cancer, the data are controversial and other studies have neither reported any association nor even shown any association between long sleep duration and cancer [50][51][52][53][54][55][56][57]. Two main reasons may explain these disparate findings.…”
Section: Sleep Duration and Cancermentioning
confidence: 87%